Extraoral Radiography as an Alternative during Covid-19 Pandemic - Sari, Anindiya Kartika; Suparno, Nilasary Rochmanita (Universitas Muhammadiyah Surakarta, 2021)
Purpose: The purpose of this literature review was made as a recommendation radiography materials for dental practitioners to use extraoral radiography as an alternative during the Covid-19 pandemic. Methodology: This literature review is created by collecting journals and case reports with keywords “extraoral radiography” and “Covid-19 pandemic”. The inclusion criteria used in this articles review are articles published in English and Bahasa Indonesia, scopus indexed articles and research articles, and also from dental radiology books. Results: Some dentistry organizations have suggested using extraoral radiography examinations as an alternative during the Covid-19 pandemic. These include panoramic, CBCT, extraoral bitewing and extraoral periapical radiography. Applications/Originality/Value: Using extraoral radiography with panoramic, CBCT, extraoral bitewing and extraoral periapical radiography can be used as an alternative in radiography examination during the Covid-19 pandemic.